From Control to Compassion: Ecohumanism as a Framework for Teaching about Invasive Species - Gal, Adiv (Journal of Ecohumanism, 2024)
This study explores the effect of the ecohumanistic approach on environmental education students’ perceptions of invasive species in Israel. The research draws on ecohumanism, a framework emphasizing the ethical responsibility humans hold toward nature, to challenge the traditional binary perspectives on invasive species. During the course of more than six years, 105 undergraduate and 127 graduate students participated in a biodiversity course, including a lecture on invasive species taught through the lens of ecohumanism. The study employed qualitative methods, using drawings, reflections, and interviews to capture students’ evolving perceptions. A thematic analysis revealed three key shifts: a). initial negative emotions and simplistic views of invasive species, b). a deeper understanding of the complexity of ecological interactions, and c). reflections on the students’ roles as future educators. Findings highlight the importance of integrating ethical and ecological perspectives in environmental education. The study concludes that an ecohumanistic framework fosters critical thinking, empathy, and responsibility, equipping future educators to address complex environmental challenges.